2018
DOI: 10.1186/s12905-018-0563-7
|View full text |Cite
|
Sign up to set email alerts
|

Sexual initiation and associated factors among young women in West Shoa, Ambo Town, Ethiopia: a community-based cross-sectional study

Abstract: BackgroundFor physiological as well as behavioral reasons, sexual debut increases young individuals’ risk for infection with sexually transmitted infection including HIV. It is fundamental to recognize the factors related to sexual debut in a broader context for designing and implementing effective interventions targeting youth.MethodsCommunity-based cross-sectional study was employed from January to May, 2013 among females of Ambo town. A multistage sampling technique was applied. The participants were select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
7
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 11 publications
(15 reference statements)
6
7
0
5
Order By: Relevance
“…Exposure to pornographic movies was one factor that promotes unhealthy sexual relationship and this study showed those who had exposure were more likely to practice risky sexual behaviors. This result was supported by different studies done in Tanzania and parts of Ethiopia (Tadesse and Yakob, 2015;Mariam et al, 2018;Nigatu et al, 2018;Kahsay et al, 2017;Yarro and Kafanabo, 2016). Nevertheless, contradictory to some studies done in Ethiopia (Alamrew et al, 2013;Ali, 2017).…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Exposure to pornographic movies was one factor that promotes unhealthy sexual relationship and this study showed those who had exposure were more likely to practice risky sexual behaviors. This result was supported by different studies done in Tanzania and parts of Ethiopia (Tadesse and Yakob, 2015;Mariam et al, 2018;Nigatu et al, 2018;Kahsay et al, 2017;Yarro and Kafanabo, 2016). Nevertheless, contradictory to some studies done in Ethiopia (Alamrew et al, 2013;Ali, 2017).…”
Section: Discussionsupporting
confidence: 59%
“…This study speculated that those individuals were more prone to risky sexual behavior. This finding correlates with studies done in parts of Ethiopia, in three Asian countries (Hanoi, Shanghai, and Taipei) and Nigeria (Negeri, 2014;Mariam et al, 2018;Nigatu et al, 2018;Fentahun and Mamo, 2014;Kahsay et al, 2017; Ifeadike et al, 2018; Mavhandu-Mudzusi and Asgedom, 2016); however, inconsistent with some studies done elsewhere (Alamrew et al, 2013, Dadi andTeklu, 2014). For this discrepancy, methodological aspects over weight other situations.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Generally, usual ratings of sexual satisfaction (Hyde, 2005;Jackson, Miller, Oka, & Henry, 2014) are not different between the genders; as several findings (Nigatu, Seme, Fituma, &Segni, 2018;O'Sullivan & Byers, 1992) suggest that gender differences exist in the meaning, perceptions and importance attached to sexual drive, sexual initiation, and sexual intimacy. Female and male sexual orientations are divergent.…”
Section: Introductionmentioning
confidence: 94%
“…Sexual initiation is perceived as the ability to influence and commence sexual activity with one's partner resulting in sexual intercourse (Nigatu, Seme, Fituma, &Segni, 2018). Various scholars (Byers & Heinlein, 1989;McCormick, 1979;Vannier& O'Sullivan, 2011) have dimensioned sexual initiation into twothe verbal and non-verbal initiations.…”
Section: Literature Review -Sexual Initiationmentioning
confidence: 99%